2009
DOI: 10.1136/vetrec.165.4.111
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and venereal disease in cattle inseminated with semen containing bovine herpesvirus type 5

Abstract: A group of 20 cows and heifers experienced poor conception rates and probable ovarian dysfunction after being artificially inseminated. When first examined, some showed signs of vulvovaginitis, with pustular, ulcerative lesions consistent with a herpesvirus infection. They had had no contact with bulls during the current breeding season. Bovine herpesvirus type 5 (BHV-5) was isolated from samples of frozen semen from the batch that had been used for the artificial insemination programme. BHV-5 was also isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Despite numerous reports of BoHV-5 in bull semen, the significance of BoHV-5 in semen is unknown [16-20]. Recently, an association between venereal disease in cows and artificial insemination with semen contaminated with BoHV-5 has been described in Australia [18,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous reports of BoHV-5 in bull semen, the significance of BoHV-5 in semen is unknown [16-20]. Recently, an association between venereal disease in cows and artificial insemination with semen contaminated with BoHV-5 has been described in Australia [18,21]. …”
Section: Introductionmentioning
confidence: 99%
“…O herpesvírus bovino -5 (BoHV-5), prevalente no Brasil (Salvador et al, 1998), tem sido primariamente associado a encefalites ou meningoencefalites em bovinos, embora já tenha sido associado a problemas reprodutivos, em alguns casos (Bratanich et al, 1991;Kirkland et al, 2009). As amostras de BoHV-5 foram também subdivididas em subtipos a, b e "não a, não b", ou "c" (D'Arce et al, 2002).…”
unclassified
“…Bovine herpesvirus 1 has been associated with respiratory tract infections (bovine infectious rinotracheitis, IBR), abortions, sporadic cases of encephalitis and reproductive tract infections (vulvovaginitis or balanopostitis) (Engels and Ackermann 1996, Muylkens et al 2007, Nandi et al 2009. Bovine herpesvirus 5 seems to be widely distributed in Latin America (Esteves et al 2008, Pidone et al 1999, Silva et al 2007, although it has been occasionally found in other regions of the world (Bartha et al 1969, Carrillo et al 1983, Diallo et al 2010, d'Offay et al 1993, Eugster et al 1975, Kirkland et al 2009. Bovine herpesvirus 5 has been associated with encephalitis and meningoencephalitis in calves and is of utmost importance in the differential diagnosis of bovine spongiform encephalitis .…”
Section: Introductionmentioning
confidence: 99%